Computational genomics of Torque teno sus virus and Porcine circovirus in swine samples from Canada. (January 2021) - Shahhosseini, Nariman; Frederick, Christina; Letourneau-Montminy, Marie-Pierre; Marie-Odile, Benoit-Biancamano; Kobinger, Gary P.; Wong, Gary
Abstract: Emerging viral diseases include pathogens that can threaten the health of the Canadian swineherd. Anelloviruses and Circoviruses comprise of pathogens with veterinary significance. The aim of this study was to determine the genomic organization and phylogenetic relationships of Torque teno sus virus (TTsusV) and Porcine circovirus (PCV) from Canadian pig samples. Fecal and tissue specimens were collected during the winter, spring and summer of 2018. We utilized either virus- or genus-specific PCR assays to characterize the occurrence and genetic diversity of TTsusV and PCV in Canadian pigs. Pairwise comparison of all partial sequences and identity calculation was performed using MAFFT algorithm implemented in Sequence Demarcation Tool (SDT). The obtained full-length sequences were aligned using ClustalW, and phylogeny was inferred using a Maximum likelihood (ML) method by Geneious software. The PCR detection results revealed that the overall positive rate of TTsusV type-1 and type-2 was 45.6% and 32.6%, respectively. The TTsusV isolate MK990454 from Canada clustered in the subtype TTsusV1b, while the TTsusV isolate MK872392 fell in the subtype TTsusV2c, and all showed similarity to known American and Chinese isolates. In addition, our screening PCR showed that 2.7% of stool samples were positive for PCV1. Phylogenetic analysis using the full-length sequence demonstrated that PCV1 (MK872393) isolated from Quebec clustered with other Chinese PCV1 strains. Despite the far geographical distance between Canada and China, the close similarity between Canadian and Chinese TTsusV1 and 2, and PCV1 sequences may be explained by a considerable amount of pig trade between these two nations. Highlights: Our aim was to determine genomic organization and phylogenetic relationships of TTsusV and PCV in Canadian pigs Canadian TTsusV1 and 2 isolates are similar to American and Chinese isolates Canadian PCV1 isolates clustered with Chinese PCV1 Similarity between Canadian and Chinese TTsusV1/2, and PCV1 can be explained by a considerable amount of pig trade